miRNA target-binding sites as regulators of genes involved in the lipid metabolism might explain the hypercholesterolaemia in FH patients - Medeiros, A.M. (2022)
Aims to analyze miRNAs target sites as regulators of genes involved in the lipid metabolism in FH mutation-negative patients.